Crystallization enhanced thermal-sensitive hydrogels of PCL-PEG-PCL triblock copolymer for 3D printing. (26th February 2021) - Cui, Yuecheng; Jin, Ronghua; Zhou, Yang; Yu, Meirong; Ling, Yun; Wang, Li-Qun
Abstract: Temperature-sensitive hydrogels with mild gel-forming process, good biocompatibility and biodegradability have been widely studied as bioinks and biomaterial inks for 3D bioprinting. However, the hydrogels synthesized via copolymerization of aliphatic polyesters and polyethylene glycols have low mechanical strength and cannot meet the needs of 3D printing. In this paper, we propose a strategy of enhancing the strength of hydrogels by introducing crystallization between blocks to meet the requirements of 3D bioprinting inks. A series of polycaprolactone-polyethylene glycol-polycaprolactone (PCL-PEG-PCL) triblock polymers were prepared by ring-opening polymerization, of which the strong crystallinity of polycaprolactone blocks improved the printability and enhanced the mechanical properties of the ink. It was found that the resulted hydrogels were temperature-responsive, and the PCL blocks could form a crystalline phase in the state of the hydrogel, thereby significantly increasing the modulus of the hydrogel. Moreover, the mechanical strength of the hydrogel could be adjusted by changing the composition ratio of each block of the copolymer. The 3D printing results showed that the PCL-PEG-PCL hydrogel with crystallinity can not only be extruded and printed via temperature adjustment, but also the three-dimensional structure can be effectively maintained after 3D printing. The gels demonstrated good cell compatibility, and the cell survival rate was maintained at a high level.